Projecting climate change impacts on chalky grain rice in East Kalimantan, Indonesia and implications for heat-tolerant rice variety breeding - AYUB PRAMANA; NURHASANAH NURHASANAH; WIDI SUNARYO; RUSDIANSYAH RUSDIANSYAH; HADI PRANOTO (Asian Journal of Agriculture, 2026)
Abstract. Pramana A, Nurhasanah, Sunaryo W, Rusdiansyah, Pranoto, H. 2026. Projecting climate change impacts on chalky grain rice in East Kalimantan, Indonesia and implications for heat-tolerant rice variety breeding. Asian J Agric 10 (1): g100147. https://doi.org/10.13057/asianjagric/g100147. Rising temperatures associated with climate change are increasing the incidence of Chalky Grain Rice (CGR), reducing grain quality. This study projects future CGR risk and identifies the level of heat-tolerance required for rice varieties to maintain acceptable grain quality under climate change in East Kalimantan, Indonesia. Future CGR incidence was simulated using a temperature-based CGR model combined with bias-corrected climate projections under Representative Concentration Pathway (RCP)2.6 and RCP 8.5 scenarios, along with simulations of rice varietal heat-tolerance under optimistic, median, and pessimistic conditions. Results indicate that even under the low-emission RCP2.6 scenario, most rice-growing areas are projected to exceed the 15% CGR threshold by the 2040s under the optimistic case. Under median conditions, substantially higher CGR levels are projected, particularly under RCP 8.5. To maintain CGR below acceptable limits, rice varieties capable of tolerating temperature increases of approximately 2-3.5°C above current conditions are required by the 2040s, while pessimistic scenarios under both RCPs demand heat-tolerance of up to 4°C. These findings highlight the urgent need to accelerate targeted breeding programs to develop heat-tolerant rice varieties capable of sustaining grain quality, meeting national standards, and remaining resilient under continued climate warming.